THE EFFECT OF EARLY MOBILIZATION EXERCISE ON THE LEVEL OF INDEPENDENCE ON PATIENTS AFTER POST OPERATIVE FRACTURE FEMUR - Widiastuti, Agung; Rahmasari, Ikrima; Budiati, Dhiani; Ermawati Ulkhasanah, Muzaroah; Yuli Kartikasari, Annisa (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2023)
Background; Patients with postoperative femur fractures will experience limited motion in their knee function, weakness, immobility and disability as a result of limitations in caring for themselves and carrying out daily activities. This study is to determine the effect of early mobilization education on the level of independence in postoperative patients with femur fracture. Research methods; The study used a quasi-experimental design with pre and post control group design, with 36 respondents (18 experimental groups, 18 controls). Data collection using questionnaires and observation. The independent variable is early mobilization education, while the dependent variable is the level of independence. The sampling technique used consecutive sampling. The population in this study were patients with postoperative at Prof. Dr. R. Soeharso Surakarta. Data analysis using independent t-test and paired t-test. Research results; There is a significant difference in the level of independence in patients before and after being given early mobilization exercises of intervention group. The results of the independent t-test on the level of independence obtained p value (0.0001) <0.05, there is a significant difference in the level of independence in patients in the control group and intervention group. Conclusion; There is an increase in independence in patients after early mobilization education, and there is a difference in the level of independence in the control group and the intervention group.